Sex-Cord Tumor with Annular Tubules with Unusual Morphology in an Infant with Peutz-Jeghers Syndrome. (4th March 2022) - Maity, Priyanka; Das, Nandini; Chatterjee, Uttara; Basak, Dhananjay
Abstract: Background Peutz-Jeghers syndrome (PJS) is characterized by hamartomatous gastrointestinal polyposis, mucocutaneous pigmentation and cancer predisposition. The clinical features of PJS manifest in first two decades of life; however, neonatal presentation is uncommon. Case report: We present a five day old girl with PJS that presented with obstructive hamartomatous polyps in the sigmoid colon. At colostomy closure at six months, an incidental ovarian sex-cord tumor with annular tubules (SCTAT) was detected. It showed predominantly a solid pattern with limited tubule formation and was composed of lipid-rich cells. She had no hormonal symptoms. Conclusion: SCTAT can occur as young as six months of age in PJS, and may show histologic overlap with lipid-rich Sertoli cell tumors.